SIESTA input and output files for calculations on the S22 data set - Carter, Damien; Rohl, Andrew (2011)
This dataset is an archive that contains a complete set of SIESTA input and output files (including pseudopotentials) for calculations on the S22 data set. In particular, this archive contains results using the PBE and vdW-DF exchange-correlation functionals, for basis sets of varying size including DZ, DZP, TZP and TZP-L. The binding energy results from these calculations have been published in a manuscript by Carter and Rohl, in the Journal of Chemical Theory and Computation.